Higher Muscle Mass Implies Increased Free-Thyroxine to Free-Triiodothyronine Ratio in Subjects With Overweight and Obesity - Zupo, Roberta; Castellana, Fabio; Sardone, Rodolfo; Lampignano, Luisa; Paradiso, Silvia; Giagulli, Vito Angelo; Triggiani, Vincenzo; Di Lorenzo, Luigi; Giannelli, Gianluigi; De Pergola, Giovanni (Frontiers in Endocrinology, 2020)
Thyroid hormones control both metabolic pathways and body composition, whereas little knowledge is available about the possible influence of skeletal muscle mass (MM) on thyroid hormone metabolism and circulating levels. This was a cross-sectional study conducted at the Population Health Unit of the National Institute of Gastroenterology IRCCS "S. de Bellis" (Italy) and investigating the extent to which skeletal muscle mass affects thyroid function in obesity. Two hundred twenty-seven consecutive healthy volunteers (155 women and 72 men) with overweight and obesity (BMI ≥ 25 Kg/m2) and taking no medication or supplement were assessed for hormone, metabolic and routine laboratory parameters. Body composition parameters were collected by using bioelectrical impedance analysis (BIA). MM was directly related to the body mass index (BMI), waist circumference (WC), insulin, triglycerides, uric acid and free-triiodothyronine (FT3) serum levels, FT3 to the free-thyroxine (FT4) ratio, and insulin-resistance (HOMA IR), and inversely related to age, total and HDL-cholesterol serum levels. Multiple regression models confirmed the relationship between MM and the FT3 to FT4 ratio, independently of age, BMI, TSH, triglycerides and insulin serum levels. The same analyses run by gender showed that this relationship maintained significance only in men. Increased skeletal muscle mass in obesity results in improved thyroid activity mediated by increased T4 conversion to T3, and higher FT3 circulating levels, particularly in men. In conclusion, preserving a greater skeletal muscle mass in obesity helps to enhance thyroid activity.